PERAN PEMERIKSAAN NON INVASIF DAN PENCITRAAN KARDIOVASKULAR DALAM MANAJEMEN PENYAKIT JANTUNG KORONER - Ricky Juliardi Mezal (HUMAN CARE JOURNAL, 2021)
Noninvasive cardiac test is a cornerstone of the diagnostic work-up in patients with suspected coronary artery disease (CAD). It is essential for the assessment of CAD and considered the gate-keeper to invasive coronary angiography. Cardiac tests include exercise electrocardiography, single photon emission computed tomography myocardial perfusion imaging, positron emission tomography myocardial perfusion imaging, stress echocardiography, coronary computed  tomography angiography, and stress cardiac magnetic resonance. However, clinicians face a challenge when deciding which test is most appropriate for a given patient. Basic knowledge of each modality will facilitate the decision-making process in CAD assessment.